Apple Fruit (Malus domestica Borkh.) Metabolic Response to Infestation by Invasive Brown Marmorated Stink Bug (Halyomorpha halys Stal.) - Tilen Zamljen; Aljaž Medič; Robert Veberič; Metka Hudina; Franci Štampar; Ana Slatnar (Horticulturae, 2021)
The brown marmorated stink bug (BMSB; Halyomorpha halys Stal.) has become a significant pest in Slovenia, especially in apple, pear, peach, and cherry orchards. In our study, apple fruit of the apple cultivar ‘Red Pinova’ were evaluated for visual injury and sugar, organic acid, and phenolic contents. The chemical composition of the area around the puncture wound, the uninjured part of the infested apple, was compared to, as a control, only uninjured apples. There was a significant response of the apple around the puncture wound, resulting in an 11.9 g/kg FW higher total sugar content, a 1.4 g/kg FW lower total organic acid content, and an 11.9 g/kg FW higher total phenolic content compared with control apples. A strong phenolic response in the puncture wound area, with high flavanol and hydroxycinnamic acid contents, with increases of 118% and 237%, respectively, compared with control apples, was detected. The brown marmorated stink bug induces a strong phenolic response in the injured area of the apple. The results of this study illustrated how apple fruit responds to the BMSB injury, not only sensorily (visual injury, odor), but also chemically in the form of metabolic responses.